The mediating role of generational difference on the relationship between psychological capital, psychological empowerment, organisational support and the wellbeing of South African National Defence Force members - Selepe, Babitsanang Annah (Rhodes University, Faculty of Humanities, Department of Psychology)
There is a growing concern in understanding the contribution of generational difference (as a mediating variable) and factors that increase soldiers' well-being. This study aimed to determine the relationship between Psychological Capital, Psychological Empowerment and Organisational Support, and well-being. Additionally, it proposes the generational differences as a potential mediating factor among these variables. The study was guided by a positivist philosophy and quantitative research method was employed. The sample for this research consisted of 777 members from both Internal deployed within borders of Free state and those going for external deployment at De-Brug. The results show most respondents were male (78.3%) and 21.7% female. Most respondents were categorised as Gen Y (between 1981 - 1996, 67.0%), followed by Gen X (1965 - 1980, 24.8%) and Gen Z (1997 - 2012, 8.2%). Most respondents were in the SA Army, followed by SAAF and SAMHS and the SA Navy. Spearman's Correlation and ANOVA analyses were conducted to test the relationship between the variables. The results revealed significant relationships between the variables included in the empirical model. However, Well-being does not have a statistically significant correlation with the mediation variable, generation cohort. Similarly, generation cohorts (X, Y, Z) do not significantly correlate with the predictor variables, Perceived Organisational Support, Psychological Empowerment. However, there is a statistically significant small negative correlation between generation cohort (Age) and Psychological Capital. The multiple regression analysis exhibited a significant overall model fit, indicating that 30% of the variance in employee well-being was accounted for by the predictors. Thus, this research implicates that the South African National Defence Force (SANDF) would benefit from developing a culture and adopting policies as well as programmes that prioritises psychological well-being above physical prowess. For this reason, the present study is regarded as offering a potentially valuable contribution to the existing body of research in the positive psychology and reveals practical implications and applications within the military context. The study recommends that combat readiness requires prioritising mental health above physical strength. Policymakers should consider psychological factors like psychological capital and psychological 6 empowerment. Training programmes should include Psychological Capital and cognitive resilience. There should also be further research on positive psychology and troops' well-being. These factors can help improve peacekeeping and combat force readiness. Understanding generational variations' mediating effect can inform resilience and training programmes. Military organisations should cultivate confident, capable, and educated leaders to improve military proficiency.
Keywords: Positive psychological capital; Perceived organizational support; South Africa National Defence Force; Intergenerational relations; Conflict of generations; Well-being -- Age factors; Soldiers -- Psychology